Extending the Boundaries of the Attest Function. - Norgaard, Corine T. (The Accounting Review, 1972)
The article presents a study designed to answer whether the attest function has already extended into new areas and whether there is evidence that the attest function will he further extended within the foreseeable future. Specifically, extensions to these areas were considered the internal control system of an entity, the efficacy with which management performs its function, financial data beyond that contained in the financial statements including financial projections, and conformance of operations to pre-determined standards, for example, actual performance to budgeted performance. Articles relevant to extensions of the attest function have tended to focus on the "pros" and "cons" of a specified extension. They have not generally been concerned with the examination of available evidence to determine whether a given extension is actually taking place or can be forecasted. The results of such an examination provide the basis for this paper. There is, with one exception, little evidence to support the contention that the attest function has extended into new areas or will be extended in the near future.